2021
DOI: 10.1186/s12888-021-03455-0
|View full text |Cite
|
Sign up to set email alerts
|

The relations between different components of intolerance of uncertainty and symptoms of generalized anxiety disorder: a network analysis

Abstract: Background Intolerance of uncertainty (IU) is considered as a specific risk factor in the development and maintenance of generalized anxiety disorder (GAD). Yet, researches have investigated the relations between IU and GAD (or worry) using total scores on self-report measures. This ignores that there are different components exist in IU and the heterogeneity of GAD symptoms. In the present study, we explored the relations among different components of IU and symptoms of GAD. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 67 publications
4
16
0
Order By: Relevance
“…The strongest edges within the IU cluster were between IU 1 (“Unforeseen events upset me greatly”) and IU 2 (“It frustrates me not having all the information I need”). These results are consistent with previous research on the network structure of IU ( 19 , 24 ). For the PSU cluster, we found PSU 2 (“Do you feel more irritability, anxiety or even sadness when you try to either reduce or stop your smartphone use”) has a strong connection to PSU 3 (“Do you feel the need to spend increasing amount of time engaged smartphone use in order to achieve satisfaction or pleasure?”).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The strongest edges within the IU cluster were between IU 1 (“Unforeseen events upset me greatly”) and IU 2 (“It frustrates me not having all the information I need”). These results are consistent with previous research on the network structure of IU ( 19 , 24 ). For the PSU cluster, we found PSU 2 (“Do you feel more irritability, anxiety or even sadness when you try to either reduce or stop your smartphone use”) has a strong connection to PSU 3 (“Do you feel the need to spend increasing amount of time engaged smartphone use in order to achieve satisfaction or pleasure?”).…”
Section: Discussionsupporting
confidence: 93%
“…It is worth mentioning the crucial role of IU 2 (i.e. as both a central node and a bridge node) was also reported in a network study that examined the relationship between IU components and generalized anxiety disorder symptoms ( 24 ). This indicates that IU 2 may be a target for research and interventions across different mental health conditions, in line with current transdiagnostic models of psychopathology (e.g., RDOC) ( 53 ).…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…This study revealed that the strongest edges appeared within the communities rather than connecting different communities. This is consistent with prior studies that have shown that the strongest edges exist within each community when detecting relationships between variables in a network consisting of two or more communities (24,53,63,(90)(91)(92)(93). For the PSU community, the two strongest positive edges were between PSU1 "salience" and PSU3 "mood modification" and between PSU4 "tolerance" and PSU6 "relapse"; this has also been found in a prior network research (24).…”
Section: Discussionsupporting
confidence: 91%
“…Within the current network, node bridge centrality may help to understand the relative importance of each MW component in relation to burnout ( 56 58 ). Addressing the bridge node could deactivate the propagation path and reduce co-occurrence ( 33 ).…”
Section: Discussionmentioning
confidence: 99%